PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN PRESTASI BELAJAR IPS SISWA KELAS V SDI ENDE 14 - Berty Sadipun (Inteligensi : Jurnal Ilmu Pendidikan, 2020)
The objectives achieved in this research are to find out the use of think pair share type cooperative learning models in Social Studies learning of Artificial Appearance in Indonesia, to find out the increase in students' learning achievement by using cooperative learning models of think pair share type in SDI Ende 14 Ende Timur district, Ende Regency. This type of research is Classroom Action Research, with a qualitative approach to grade 5 students of SDI Ende 14. Data collection techniques in this study were observation, interviews, learning outcomes tests and documentation. Data analysis uses descriptive qualitative data analysis techniques. Based on the results of the evaluation of the first cycle with a percentage of completeness of 54% and an average of 57.45%, the results of the evaluation of the second cycle with a percentage of completeness of 100% with an average of 90%, the application of the cooperative learning model type think pair share with the material appearance made in Indonesia can improve student learning achievement.